Political Perception, Turnover Intention, and Negligent Behavior of Private Employees in Aceh - Rusdi Rusdi; Muhammad Rahmat Hidayat; Fajri Hadi; Fatmayanti Fatmayanti (Mahesa Research Center, 2025)
This study examines the relationship between perception of politics, job stress, job satisfaction, negligent behavior, turnover intention, and self-reported absenteeism in the work environment. The analysis results show that politics significantly affects job stress and satisfaction, whereas a positive political perception can reduce and increase job satisfaction. Job stress was found to hurt job satisfaction, which ultimately increased negligent behavior in the workplace. Additionally, job satisfaction is vital in reducing negligent behavior and self-reported absenteeism, underscoring the importance of organizational efforts in improving employee satisfaction. In contrast, turnover intention did not significantly correlate with negligent behavior or self-reported absenteeism, suggesting other factors may influence this intention. These findings emphasize the importance of building a positive political perception in the workplace, managing job stress, and increasing job satisfaction to create a more productive and conducive work environment. The study also shows that some relationships between variables are not always significant, so more research is needed to understand more complex interactions in the work environment.